The Impact on Federal Spending of Allowing the Terrorism Risk Insurance Act to Expire - LaTourrette, Tom (RAND Corporation, 2014)
Congress enacted the Terrorism Risk Insurance Act (TRIA) in response to the terrorism insurance industry contraction after the 9/11 attacks. With TRIA set to expire, this policy brief examines the federal spending implications of TRIA. The authors find that, in the absence of a terrorist attack, TRIA costs taxpayers relatively little, and in the event of an attack comparable to any experienced before, it is expected to save taxpayers money.